2022
DOI: 10.1136/rapm-2022-103723
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of labor analgesia efficacy between single-orifice and multiorifice wire-reinforced catheters during programmed intermittent epidural boluses: a randomized controlled clinical trial

Abstract: AimsWe compared analgesic outcomes between single-orifice and multiorifice wire-reinforced catheters under 480 mL/hour delivery rate with programmed intermittent epidural bolus administration.MethodsBetween August and November 2021, 182 nulliparous and healthy women with singleton pregnancy, 2–5 cm cervical dilation, and requesting neuraxial analgesia were randomized to receive either single-orifice or multiorifice catheters. Epidural analgesia was initiated and maintained with 0.1% ropivacaine and 0.3 µg/mL s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Thus, the percentage of sufficient analgesia 15 min after the initial volume is selected as the primary outcome, which is similar to a recent study. 24 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the percentage of sufficient analgesia 15 min after the initial volume is selected as the primary outcome, which is similar to a recent study. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Because the fetal heart monitoring can be diverse in the whole stages of labor owing to the complex personal situation, and studies have shown that epidural analgesia has little statistical influence on fetal heart rate, we will not analyze it. 5 , 19 , 24 However, we will collect the apgar score to evaluate the security of neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation